FAKTOR-FAKTORYANG MEMPENGARUHI PERMINTAAN PINJAMAN DANA PADA KOPERASI PEGAWAI NEGERI „SINKA‟ DI KOTA SINGKAWANG - B01107087, Riandi (Jurnal Pembangunan dan Pemerataan, 2015)
This study entitled 'Factors Affecting Demand Loan Fund In Cooperative Servants' Sinka' In Singkawang ". This study uses as many as 200 respondents. The purpose of thisstudy was to determine the factors that affect the demand for loans in the Civil ServiceCooperative (KPN) 'Sinka' Singkawang This study uses quantitative analysis, ie, by classifying the answers from thequestionnaire results are then summed and tabulation were presented. The factors are examined based on the results of questionnaires, among other factorsin choosing a loan cooperatives, economic, non-economic factors, so in the know the factorsthat affect loan demand on the cooperative 'Sinka'. Key word:  cooperative, demand, loan